Validation of analytical methods and detection limits in spectroscopic measurements of Ag–Cu alloys - Gójska, Aneta Maria (Radiation physics and chemistry (Oxford, England : 1993), 2025)
This study investigates the K-X-ray spectra of Ag–Cu alloys using Energy Dispersive X-ray Fluorescence and Wavelength Dispersive X-ray Fluorescence spectrometers. The research focuses on the detection limits of silver and copper, induced by a Rhodium X-ray tube, and explores the dependence of these limits on the sample matrix. Various detection limits, such as the Lower Limit of Detection, Instrumental Limit of Detection, Minimum Detectable Limit, Limit of Detection, and Limit of Quantification, are defined and compared. Different Ag–Cu alloys with varying compositions were analyzed, with results indicating that detection limits are significantly influenced by the matrix composition. Calibration lines for silver and copper were established, showing strong linearity for silver and a cubic fit for copper. The validation process, which included accuracy and recovery assessments, confirmed the reliability and precision of the analytical methods used. This study provides valuable insights into the spectroscopic analysis of Ag–Cu alloys, offering a detailed examination of detection limits and validation procedures, which can inform future research and practical applications in related fields. •A comprehensive analysis of the K-X-ray spectra of Ag–Cu alloys was conducted using ED-XRF and WD-XRF spectrometers.•An evaluation and comparison of multiple detection limits: LLD, ILD, CMDL, LOD, and LOQ were performed.•It was shown that the matrix composition significantly affects the detection limits of silver and copper.•The results have practical implications for elemental analysis in material science, geology, and other fields.•The need for careful consideration of matrix effects when applying LLD formulas was emphasized.